Mesoporous activated carbon fibers synthesized from denim fabric waste: Efficient adsorbents for removal of textile dye from aqueous solutions. (10th January 2018) - Silva, Taís L.; Cazetta, André L.; Souza, Patrícia S.C.; Zhang, Tao; Asefa, Tewodros; Almeida, Vitor C.
Abstract: Denim fabric waste was used as a carbon precursor, and chemically activated with phosphoric acid in the ratio of 1:1 ( v:m ) under a slow pyrolysis process to obtain activated carbon fibers (ACFs). The chemical and physical properties of the ACFs were investigated from the thermogravimetric analysis (TGA), N2 porosimetry, scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), Raman and Fourier transform infrared spectroscopy (FTIR), Boehm titration method, and point of zero charge ( pH PZC ). The obtained ACFs showed high yield (53%), BET surface area of 1582 m 2 g −1, mesoporous features (average pore diameter of 3.60 nm), and surface acidic properties ( pH PZC value of 2.13 and 1.13 mmol g −1 of acidic groups). The ACFs were applied in the removal of textile dye, Remazol Brilliant Blue R (RBBR), from aqueous solution. The adsorption isotherm and kinetic studies showed that adsorption of RBBR on the ACFs were better described by the pseudo-second order kinetic model and the Freundlich equilibrium model. The maximum adsorption capacity of the ACFS for RBBR was determined to be 292 mg g −1, which is higher than other adsorbent materials reported in the literature. The adsorption thermodynamic parameters indicated that adsorption process is spontaneous and exothermic. Graphical abstract: Highlights: ACFs were synthesized from denim waste and H3 PO4 with slow pyrolysis. ACFs showed SBET value of 1582 m 2 g −1 and mesoporosity features. BJH method showed a narrow pore distribution and average diameter of 3.6 nm. Adsorption studies for removal of RBBR from solutions were successfully performed. ACFs showed a maximum adsorption capacity of 292 mg g −1 at 25 °C for RBBR.